2017
DOI: 10.1515/fhort-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds, bioactive content and antioxidant capacity of the fruits of mulberry (Morus spp.) germplasm in Turkey

Abstract: The study was carried out in 2014 and 2015, and aimed to determine some important biochemical and antioxidant characteristics of the fruits of mulberry (Morus spp.) cultivars and genotypes found in Malatya (Turkey). Phenolic compounds (protocatechuic acid, vanillic acid, ellagic acid, rutin, quercetin, gallic acid, catechin, chlorogenic acid, caffeic acid, syringic acid, p-coumaric acid, o-coumaric acid, phloridzin and ferulic acid), organic acids, sugars, vitamin C and antioxidant capacity were analyzed in sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 28 publications
2
27
0
1
Order By: Relevance
“…Dry mulberry leaves exhibited DPPH radical scavenging activity as 18.1 mg TE/g DM. This agrees with a recent study of Sánchez-Salcedo et al [25] showing slightly lower radical scavenging activity amounting till 12.64 mg TxE/g DW. The water extraction process caused more than fivefold increase of antioxidant activity.…”
Section: Resultssupporting
confidence: 94%
“…Dry mulberry leaves exhibited DPPH radical scavenging activity as 18.1 mg TE/g DM. This agrees with a recent study of Sánchez-Salcedo et al [25] showing slightly lower radical scavenging activity amounting till 12.64 mg TxE/g DW. The water extraction process caused more than fivefold increase of antioxidant activity.…”
Section: Resultssupporting
confidence: 94%
“…Sugar content of mulberry genotypes (mean for 2016 and 2017 ±SE) Genotypes Glucose (g 100 g -1 ) Fructose (g 100 g -1 ) Sucrose (g 100 g -1 ) 64USA01 9.13 ±0.16 b* 6.54 ±0.12 e 1.51 ±0.03 c same study, citric acid, tartaric acid, succinic acid and fumaric acid contents were found to range from 0.48 to 1.03 g 100 g -1 , 0.15 to 0.43 g 100 g -1 , 0.12 to 0.44 g 100 g -1 , and 0.01 to 0.12 g 100 g -1 , respectively. Gundogdu et al (2017) found caffeic acid (21.09-2.44 mg 100 g -1 ), syringic acid (11.91 -1.16 mg 100 g -1 ), and p-coumaric acid (5.67-0.70 mg 100 g -1 ). In this study, it was determined that the genotypes 64USA01, 64USA07, 64USA08, 64USA10 showed desirable features when compared to other genotypes in terms of phenolic compounds.…”
Section: Organic Acidsmentioning
confidence: 94%
“…The Morus nigra L. species exists almost everywhere in Anatolia and is represented by wildelderly trees (Gundogdu et al, 2017). The height of mulberry trees is 3-15 m, and they have a splayed, rounded, clustered crown structure.…”
Section: Introductionmentioning
confidence: 99%
“…Species within each of these three states are important genetic sources of biodiversity, which support the diverse array of life on earth. [1][2][3][4][5] Wild black mulberry is a valuable resource in medicinal chemistry, gaining importance for its potential to prevent and treat diseases. [6] Mulberry (Morus, Moraceae) grows across an extensive range of climatic, topographical, and soil conditions.…”
Section: Introductionmentioning
confidence: 99%